THE EFFECT OF WORKLOAD, WORK STRESS AND COLLEAGUE SUPPORT ON EMPLOYEE PERFORMANCE AT PT LENTERA PROSPER INDO - Muktifani, Ajeng Aprilia; Hazmi, Shadrina (Count : Journal of Accounting, Business and Management, 2024)
This research investigates the relationship between three workplace factors - workload, work stress, and colleague support, and how they impact employee job performance through empirical analysis. The research framework incorporates workload, work stress, and colleague support as predictor variables, with employee job performance as the outcome variable. The research population comprised 150 full-time employees at PT Lentera Prosper Indo. Research data was gathered through on-site questionnaire distribution to participants. The investigators employed multiple linear regression techniques, complemented by t-test and F-test procedures for hypothesis verification. The findings revealed that both workload and work stress demonstrated significant adverse effects on employee job performance. Conversely, colleague support exhibited a substantial beneficial influence on employee job performance.